Avaliação funcional de interações sociais favoráveis e desfavoráveis à inclusão de crianças em escola regular - Junqueira, Priscila Haanwinckel (2013)
Research shows that children with visual handicap may develop isolation and other difficulties in social interactions, which may disrupt the process of inclusion in school. The theoretical and practical field of social skills shows that such interactions can be classified as pro- and noninclusive behaviors. Also, the frequency of such behaviors depend on the interactions (or lack thereof) between teacher and student, which are usually established by the teacher. There is currently a lack of observational studies in social skills and social competence. Thus, it is important to examine the social interaction of blind children in the school environment -- in particular using direct observation, since this method provides important data to perform a functional evaluation of pro- and noninclusive behaviors that will identify conditions that are both favorable and unfavorable to the process of inclusion. Direct observation was complemented by reports from parents and teachers, as well as self-reports and sociometric evaluations. This study aimed to: (1) Functionally describe the pro- and noninclusive social performances of two blind children in interaction with their peers and teachers in terms of antecedents and consequences; (2) Define, through measuring scales: the social skills repertoire, behavior problems, academic competence, and the sociometric status of included children; (3) Link pro- and noninclusive behaviors to social skills indicators, behavior problems, and sociometric status of children. The study participants were two children, a boy and a girl, both nine years old and diagnosed with congenital blindness. Participants were enrolled in public, regular education schools, and were filmed in the classroom environment during Portuguese classes and free activities suggested by the researcher. The observed performances were described in terms of antecedents, responses and consequences, and the percentage of correlation between the responses and events was identified. The Social Skills Evaluation System (SSRS-BR) was used with parents and teachers, as well as with the children, to obtain information on the children's behaviors. Furthermore, the children's classmates underwent a sociometric evaluation. The analysis of data collected through direct observation of behavior indicates that around 70% of performances emitted in classroom interactions were classified as proinclusive. This information is contradictory when compared to data from SSRS-BR and from sociometric evaluation. In general, the observed children were socially competent in their social interactions at school, which does not guarantee their full inclusion in this environment.